GE_GERICHTE P/5529/2011 vom 6. November 2014 - GE Cour de justice (2014)
SÉQUESTRE(MESURE PROVISIONNELLE); QUALITÉ POUR RECOURIR; BANQUE; RECOURS JOINT; CONFISCATION(DROIT PÉNAL); SOUPÇON; CRÉANCE; PROPORTIONNALITÉ | CPP.382.1; CPP.401; CPP.197.1.B; CPP.263.1.D; CPP.267; CP.70.1; CP.70.2; CP.71.1; CP.71.3